Methodology of Teaching the Science of Microbiology at the Central Asian Medical University (International Journal of Scientific Trends, 2025)
The teaching methodology of microbiology in medical higher educational institutions plays a crucial role in shaping the knowledge and practical skills of future medical professionals. This article explores the contemporary approaches to teaching microbiology, the relevance of the subject in the context of modern medical education, and the experimental methodologies used in its instruction. The paper highlights the importance of integrating innovative pedagogical methods, such as interactive learning, digital tools, and laboratory-based instruction, to enhance the learning experience. The relevance of microbiology in medical training is examined, especially in light of its application in diagnosing and treating infectious diseases. Additionally, the research investigates the main research objects and methodological approaches to teaching microbiology, including the role of practical exercises, case studies, and interdisciplinary collaboration. The article emphasizes the importance of a balanced approach to theory and practice, as well as the use of modern technological resources in the educational process.